FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA PT. INDORAYA MULIA TOUR AND TRAVEL DI KOTA PEKANBARU PROVINSI RIAU - Mega Silvia Napitupulu; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research is to know what are factors that influence employees perfomance at PT.Indoraya Mulia Tour and Travel in Pekanbaru City Riau Province and what is the most dominant factor that influence employees perfomance at PT.Indoraya Mulia Tour and Travel in Pekanbaru City Riau Province.This research used descriptive quantitative method to analyze the problem. The samples in this research are consist of 10 respondents. While data collection techniques in this study using observation, questioner, and interviews. By using a Likert scale as a measure to determine the length of the short interval.Based in the result of the research, there are three factors that influence employees perfomance at PT.Indoraya Mulia Tour and Travel in Pekanbaru City Riau Province is internal factors employee, internal factors organization and external factors organization. Factor that most dominant was internal factor employee from the indicator physical dan physchological, factor that most dominant was internal factors organization from the indicator working climate and Factor that most dominan was external factors organization from the indicator culture and religion communities.Keywords : human resource, perfomance, factors that influence the employees perfomance.